Sobolev Embeddings for Generalized Riesz Potentials of Functions in Morrey Spaces L(1, φ)(G) over Nondoubling Measure Spaces. (11th April 2013) - Sawano, Yoshihiro; Shimomura, Tetsu
Abstract : Our aim in this paper is to deal with the Sobolev embeddings for generalized Riesz potentials of functions in Morrey spaces L ( 1, φ ) ( G ) over nondoubling measure spaces.